THE EFFECT OF POLARIZED LIGHT ON THE BLOOD COAGULATION AND FIBRINOLYSIS - Коковська, О.В. (World of Medicine and Biology, 2015)
The findings of the in vitro experiments (1st stage) showed that polarized light prolonged the time of fibrinolysis of thrombocyte and thrombocyteless plasma. Such effect of polarized light is connected with the direct impact onto plasmin. The findings of the in vivo experiments (2nd stage) were more significant. In this case the effect of polarized light enhanced the blood hemostatic potential, indicated by shortening of the total time of blood coagulability from 487,3 s to 360,0 s (р